Examining Associations Between School Connectedness, Social Support, Violence, and Firearm Carrying - Pulavarthi, Teja Sai (Journal of interpersonal violence, 2024)
Firearms are the leading cause of pediatric deaths. Few studies have identified protective factors that reduce the risk of firearm violence. Interpersonal factors, including school connectedness and social support, protect against multiple health-affecting risk behaviors. Therefore, this study examines associations of school connectedness and social support with firearm and weapon violence involvement. Data were gathered through an anonymous survey conducted across 13 high schools within an urban school district in 2018 (n = 2,604) modeled on the Centers for Disease Control and Prevention Youth Risk Behavior Surveillance Survey. Separate hierarchical logistic regression models examined associations between school connectedness and social support, and the outcomes of firearm carrying and engaging in violence with a weapon on school property in the past 12 months. Models were adjusted for age, race, and covariates representing basic needs, education, and mental health. The mean age was 15.7 years, and 57.5% of youth were female. 5.8% of youth had carried firearms and 5.5% engaged in violence with a weapon on school property in the past 12 months. School connectedness was significantly inversely associated with engaging in violence with a weapon on school property (odds ratio [OR] 0.225, 95% confidence interval [CI] [0.080, 0.632] and high levels of social support were significantly inversely associated with firearm carrying (OR 0.522, 95% CI [0.313, 0.870]). School connectedness and social support may be important in protecting youth from firearm and weapon-related violence. Interventions that strengthen safe and supportive interpersonal relationships within school environments and broader support systems across contexts may help reduce firearm and weapon violence involvement.